The Effects Of Transformational Leadership, Power Distance, Communication, and Followership On Employee Decision Making - Maharani, Maulidya Dita; Achyani, Fatchan (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to determine the effect of transformational leadership, power distance, communication and followership on employee decision making. The type of research used in this study is research with a quantitative approach. Population in this study using the population census where employees at the Office of manpower, investment, and Integrated Services One Door Banjarnegara as many as 59 people. This study used primary data obtained by distributing questionnaires. To produce alternative answers this study uses a Likert scale. This study used slovin formula for sampling. The results of this study showed that transformational leadership, power distance does not affect employee decision making, while communication and followership affect employee decision making.